(untitled) - Hibbeler, R. C. (New Jersey, 2004)
A comprehensive and well-illustrated introduction to theory and application of statics and mechanics of materials. This book presents a commitment to the development of problem-solving skills and features many pedagogical aids unique to Hibbeler books. Chapter topics include general principles, force vectors, equilibrium of a particle, force system resultants, equilibrium of a rigid body, structural analysis, internal forces, friction, center of gravity and centroid, movements of inertia, virtual work, stress, strain, mechanical properties of materials, axial load, torsion, bending, transverse shear, combined loadings, stress transformation, strain transformation, design of beams and shafts, deflections of beams and shafts, buckling of columns, and energy methods. For engineering mechanics.
Keywords: Strength of materials,Statics,Structural analysis (engineering)